2013
DOI: 10.1111/maq.12048
|View full text |Cite
|
Sign up to set email alerts
|

For the Sake of our Children: Hispanic Immigrant and Migrant Families’ Use of Folk Healing and Biomedicine

Abstract: This article documents beliefs among Hispanic immigrant and migrant families in central Washington State about the etiology, symptomology, and appropriate treatments for illnesses experienced by their young children. Similar information was gathered from health care staff at several area biomedical facilities. We integrate data from the childhood health project and the authors' previous research to refine the ethnomedical knowledge base and assumptions about the impact of migration histories and acculturative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…However, physicians were not perceived as effectively treating culturally-based conditions such as empacho or espanto because they did not understand the conditions, unlike sobadores or curanderos . This position is consistent with perceptions reported by Latino immigrants and migrants in other regions of the United States [34]. The challenge for participants was to determine whose service was needed for which condition.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, physicians were not perceived as effectively treating culturally-based conditions such as empacho or espanto because they did not understand the conditions, unlike sobadores or curanderos . This position is consistent with perceptions reported by Latino immigrants and migrants in other regions of the United States [34]. The challenge for participants was to determine whose service was needed for which condition.…”
Section: Discussionsupporting
confidence: 82%
“…They perceived that sobador knowledge and skill varied widely; knowledge about sobador quality is therefore important. Although not in reference to sobadores , researchers have reported that Latinos living in other regions of the United States note the importance of determining traditional healers’ skill and knowledge [3436]. Participants considered doctors to be professionals due to their access to crucial technology such as X-ray machines, and advanced education.…”
Section: Discussionmentioning
confidence: 99%
“…These results are most comparable to those reported by Lopez, 10 with our participants making substantial but somewhat greater use of curanderos and sobadores , and somewhat less use of yerberos . Like results reported by Andrews and colleagues 18 and Lopez, 10 both Latino farmworkers and non-farmworkers had made greater use of sobadores compared to other types of traditional healers. These results show greater numbers using traditional healers than reported by Skaer and colleagues.…”
Section: Discussionsupporting
confidence: 58%
“…Description of the activities of Latin American sobadores among immigrants to the US has largely focused in areas with long Latino traditions. These areas include southern California [6, 8, 9], central and eastern Washington state [7, 14], Arizona [15], and south Texas [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Chavez surveyed Mexican immigrants to San Diego, California, on past use of curanderos , spiritualists, witches, and sobadores , and found sobadores to be the highest at 6 % [9]. Andrews and colleagues, interviewing mothers concerning child health, found about a third used sobadores , 8 % curanderos , and none used herbalists or spiritualists [14]. Although some of these studies that used survey methods also collected some additional ethnographic and qualitative data, the focus on multiple healer types and the age of some of these studies provides little information with which to understand the use of sobadores today in the US outside the traditionally Latino areas.…”
Section: Introductionmentioning
confidence: 99%